Polygenic Score for Physical Activity Is Associated with Multiple Common Diseases. Issue 2 (February 2022) - SILLANPÄÄ, ELINA; PALVIAINEN, TEEMU; RIPATTI, SAMULI; KUJALA, URHO M.; KAPRIO, JAAKKO
ABSTRACT: Introduction: Genetic pleiotropy, in which the same genes affect two or more traits, may partially explain the frequently observed associations between high physical activity (PA) and later reduced morbidity or mortality. This study investigated associations between PA polygenic risk scores (PRS) and cardiometabolic diseases among the Finnish population. Methods: PRS for device-measured overall PA were adapted to a FinnGen study cohort of 218, 792 individuals with genomewide genotyping and extensive digital longitudinal health register data. Associations between PA PRS and body mass index, diseases, and mortality were analyzed with linear and logistic regression models. Results: A high PA PRS predicted a lower body mass index ( β = −0.025 kg·m −2 per one SD change in PA PRS, SE = 0.013, P = 1.87 × 10 −80 ). The PA PRS also predicted a lower risk for diseases that typically develop later in life or not at all among highly active individuals. A lower disease risk was systematically observed for cardiovascular diseases (odds ratio [OR] per 1 SD change in PA PRS = 0.95, P = 9.5 × 10 −19 ) and, for example, hypertension [OR = 0.93, P = 2.7 × 10 −44 ), type 2 diabetes (OR = 0.91, P = 4.1 × 10 −42 ), and coronary heart disease (OR = 0.95, P = 1.2 × 10 −9 ). Participants with high PA PRS had also lower mortality risk (OR = 0.97, P = 0.0003). Conclusions: Genetically less active persons are at a higher risk of developing cardiometabolic diseases, which may partly explain the previously observed associations between low PA and higher disease and mortality risk. The same inherited physical fitness and metabolism-related mechanisms may be associated both with PA levels and with cardiometabolic disease risk. Abstract : Supplemental digital content is available in the text.